1998
DOI: 10.1097/00005176-199801000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hemochromatosis: Outcomes of Pharmacologic and Surgical Therapies

Abstract: Neonatal hemochromatosis carries a grim prognosis; however, successful OLTX is curative. The use of an antioxidant-chelation cocktail did not improve outcome in the patients studied. Earlier (perinatal) diagnosis may be required for optimal results. Further study of other interventions, including antenatal diagnosis and earlier institution or modification of cocktail therapy appears warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 10 publications
1
96
0
5
Order By: Relevance
“…15 It may be a phenotype resulting from any of a number of different causes. [15][16][17] The observation of a clinical and histologic picture consistent with neonatal iron storage disease in 4 children in this series may indicate that NLE should be sought in "idiopathic" cases of neonatal iron storage disease.…”
Section: Discussionmentioning
confidence: 81%
“…15 It may be a phenotype resulting from any of a number of different causes. [15][16][17] The observation of a clinical and histologic picture consistent with neonatal iron storage disease in 4 children in this series may indicate that NLE should be sought in "idiopathic" cases of neonatal iron storage disease.…”
Section: Discussionmentioning
confidence: 81%
“…It has been observed that some infants diagnosed with NH are affected less severely, which may account for the ϳ20% who survive with medical therapy and the very few who have no liver failure. 7,17,20 It follows that there may even be some who have no clinical evidence of disease. On testing, we found twin B to have clear-cut evidence of liver disease, with high AFP and ferritin levels, therefore supporting our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Survival of liveborn infants with liver failure is Ͻ20% with medical therapy alone. 17,20,29 In addition, the use of the cocktail is not without risk, particularly the risk of sepsis with deferoxamine. 1 Fully 50% of newborns we have treated with this cocktail have developed bacterial sepsis.…”
Section: E882mentioning
confidence: 99%
“…There is a spectrum of disease, and some infants recover with supportive care. 23,24 Indeed, it may be that some "affected" infants have no clinical disease. We have shown that twins may have disparate clinical findings, with one severely affected and the other minimally so.…”
Section: Neonatal Hemochromatosismentioning
confidence: 99%
“…Success rates with medical treatment have been reported to be 10% to 20%, though it is not clear what factors determine a successful outcome. 23,24 No controlled trial of the use of this cocktail has been undertaken. Within the spectrum of severe NH, it may be that patients with more hepatic reserve profit from it, while more severely affected patients fail to respond.…”
Section: Neonatal Hemochromatosismentioning
confidence: 99%